Avanços inovadores na análise e detecção dos genótipos da beta-caseína A1 e A2 em leite bovino: técnicas cromatográficas, peptídeos miméticos e bioeletrodos - Peres, Phelipe Augusto Borba Martins (2024)
The beta-casein A2 variant has been gaining prominence in recent years due to its potential impact on human health and the dairy industry. Unlike beta-casein A1, milk with the A2 variant does not generate betacasomorphin-7 (BCM-7) when digested in the stomach. This opioid peptide is associated with several effects on human health, such as intestinal discomfort and inflammation. Hence the relevance of the A2 variant in the market, due to consumers' incessant search for healthy foods. In view of this, the dairy industry has increased the demand for this variant in milk, investing in genotyping techniques for the genetic selection of the best animals, encouraging science to develop new tools. Studying these selection tools not only drives science, but also ensures the preservation of health by meeting the demands of a changing global market. The objective of this thesis was to develop methodologies capable of assisting in the selection of genotypes for beta-casein A1 A2 in cattle. Divided into five chapters, we structured this thesis. In the first chapter, we present a theoretical framework on the bovine genetic history for beta-casein and the techniques used for animal selection. In the second, we present a scientific article using mass spectrometry to study differential lipids in the milk of A1A1, A2A2, and A1A2 animals. In the third chapter, we present a patent filed for the development of a colorimetric kit for the differentiation of A1A1 and A2A2 milk types. In the fourth chapter, we present another scientific article, where we selected mimetic peptides using Phage Display, capable of differentiating the A2 variant. And finally, another patent that presents a bioelectrode constructed with the peptide from the article in the fourth chapter, capable of differentiating A1 and A2 beta-caseins. Finally, our findings present a promising application for the dairy market, capable of assisting or even replacing traditional methods of detecting genotypes in the field.